Ribbit! - Folgueira, Rodrigo, 1972-; Bernatene, Poly (New York : Alfred A. Knopf, 2012)
When a pig visits a frog pond, sits on a rock, and says only "Ribbit!", news spreads fast but only the wise old beetle has an explanation.
School Library Journal, March 2013
Publisher's Weekly, February 2013
Booklist, March 2013
Bulletin (Center for Children's books), June 2013
Kirkus Review, February 2013
3.4
Keywords: Pigs -- Fiction; Animals -- Fiction; Friendship -- Fiction; Pigs -- Fiction; Animals -- Fiction; Friendship -- Fiction